APLIKASI FUZZY DALAM OPTIMALISASI TRAFFIC LIGHT PERSIMPANGAN JUANDA - Ramadhani, Rahma; Ummah, Imamatul; Amudi, Abdiyah; Yannuansa, Nanndo (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
Traffic Jam is a problem that often occurs in transportation problems. Juanda Junction is one of theintersections that often experience traffic jam. The causes of traffic jam arise from many things, includingthe presence of side barriers, the absence of markers so that the traffic light that works is not optimal.Based on the results of the initial survey, it was found that the duration of the green light in each pendekawas not adjusted for how many cars and motorcycles were passing. North approacher where most cars andmotorbikes are passing but get fewer duration of green lights than other approaches. This shows lessoptimal traffic light settings. The use of fuzzy method is expected to make traffic light settings moreoptimal because the old green light produced is more flexible in accordance with many cars andmotorcycles that pass through an approach. The results of the study were obtained for vehicles passingthrough the northern approacher as many as 26 cars and 177/cycle obtained manually by the green light for43 seconds and with fuzzy 45 seconds. Western approacher with many vehicles passing by 25 cars and170/cycle motorbikes received a 51-second manual green light and fuzzy 42 seconds. As well as for theeast approacher with many vehicles passing 24 cars and 168 motorcycles/cycle get the green lightmanually 53 seconds and with fuzzy 42 seconds. Key Words: Fuzzy, Junction, Traffic Light